The Role Of Trust On Increasing Patient Satisfaction - Arbain Sandi, Nadilla Ramadhan; Noor, Noer Bahry; AS, Andi Indahwaty; Pasinringi, Syahrir Andi; Anggraeni, Rini; Kadir, Abdul Rahman (Journal of Neonatal Surgery, 2025)
Background: Patient trust in hospitals is an important factor in creating positive long-term relationships between patients and healthcare providers. A high level of trust can increase perceptions of service quality, thus having a direct impact on patient satisfaction levels. Aim: This study aims to analyze the relationship between trust and inpatient satisfaction at RSUD Syekh Yusuf in Gowa Regency. Method: Quantitative research employing Cross Sectional methodology was conducted at Syekh Yusuf Hospital's Inpatient Installation in Gowa Regency. The study included 145 participants selected through Accidental Sampling methods. Researchers collected data via questionnaires and applied chi-square testing with multiple linear regression analysis to examine variable relationships and identify key outcome predictors. Results: Trust (p = 0.013) has a significant relationship with patient satisfaction, where increasing patient trust in Syekh Yusuf Regional Hospital can increase their satisfaction with the services provided. Conclusion: Fostering patient-hospital trust substantially enhances satisfaction levels. Implementing service excellence training, digital marketing strategies, regular internal evaluations, and accessible feedback mechanisms significantly improves patient experience. These approaches strengthen service quality while developing stronger patient-hospital relationships.